PENGARUH MANAJEMEN RISIKO DAN AKTIFITAS AUDIT INTERNAL DALAM MITIGASI FRAUD - ZURMAN, ZURMAN; ULI, DESTI MONIKA (Fakultas Ekonomi Universitas Islam Indragiri, 2024)
Workplace fraud is the largest and most costly financial crime in the world. A recent ACFE report revealed that companies suffered a 5% loss due to fraud, with an average loss per case of 1.7 million USD. Not only financial losses, fraud can also provide non-financial losses. Therefore, companies need fraud mitigation (FM). FM is one of the mechanisms to overcome fraud. Some literature on FM emphasizes the importance of internal audit activities (AAI) and risk management (MR) to prevent, detect and mitigate fraud. This study aims to determine how MR, AAI affect FM and whether AAI mediates MR with FM. The sample of this study amounted to 384 people. The analysis method used is SEM analysis based on Partial Least Square (PLS). This study has proved that statistically Risk management (MR), internal audit activity (AAI), and fraud mitigation (FM) have a close relationship and support each other in creating effective organizational governance.